Photodegradation of Dyes Using Titanium Dioxide Supported on Glass - Lee, Kong Hui (2002)
Photodegradation of dyes, in aqueous solution was carried out using titanium dioxide coated on glass plates, illuminated by blue fluorescent lamps. TiO₂ coated glass was prepared by sol-gel technique. Air was pumped into the mixture to ensure continuous supply of oxygen in the mixture. Methylene blue removal was studied based on the effect of amount of coated TiO₂ sol-gel, initial concentration, light intensity, light source, and pH of solution medium. Comparison was also made to the powder form of TiO₂ which was prepared by the same method. The highest percentage of methylene blue removal was obtained when the photodegradation experiment was run using 5 pieces of TiO₂/Glass (4 times of sol-gel dip-coating) and 10 ppm of methylene blue solution at 28°C after illumination under 4 white fluorescent lamps of 20 W for 4 hours. About 84% of methylene blue was removed. Methylene blue removal was found to be efficient and comparable to the illumination using near UV light, sunlight, 4 white fluorescent lamps, 4 dark fluorescent lamps and 4 blue fluorescent lamps.